English Department Students’ Stress Levels and Their Responses Towards Online Learning - Nurhajatin Nurhajatin; Kamaluddin Kamaluddin; Nurnia Nurnia (Halu Oleo University, 2021)
This study examined whether stress level varied with gender and year of enrolment, whether there is a correlation between students’ stress level and their responses towards online learning, and examined students’ responses towards online learning in general. A total of 92 students were recruited for this study. Statistical analyses indicated that there was a significant difference in the stress level of male and female students, in that females had a significantly higher stress level than males (p=0.009). No significant differences were observed in stress level based on the academic years (year of enrolment). However, a significant negative correlation was observed between students’ stress level and their responses towards online learning